2020
DOI: 10.1111/head.13823
|View full text |Cite
|
Sign up to set email alerts
|

Modifications to the PREEMPT Protocol for OnabotulinumtoxinA Injections for Chronic Migraine in Clinical Practice

Abstract: ObjectiveTo assess the PREEMPT protocol modifications that have developed in clinical practice over time.BackgroundThe United States Food and Drug Administration approved the 155‐unit fixed‐dose, fixed‐site PREEMPT protocol of onabotulinumtoxinA (BoNT‐A) injections for migraine prevention 9 years ago.MethodsThis is an anonymous survey with free text response options of Headache Medicine clinicians.ResultsOut of the 878 contacted Headache Medicine clinicians, 182 (20.7%) completed the survey. Of the 182 respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…[17][18][19] These results demonstrate more than 10 years of robust efficacy, safety, and clinical and real-world effectiveness data supporting the use of onabotulinum-toxinA for the treatment of chronic migraine using the PREEMPT protocol. Although the authors pose the question "whether evidence-based advisory statements might be more helpful than a proscriptive protocol," 1 we suggest that, in contrast, there is robust evidence to support the PREEMPT protocol and its specific instructions and flexibility in dosing and injection sites that allow clinicians to use their judgment and tailor treatment to their individual patients.…”
Section: This Is An Open Access Article Under the Terms Of The Creativementioning
confidence: 81%
See 3 more Smart Citations
“…[17][18][19] These results demonstrate more than 10 years of robust efficacy, safety, and clinical and real-world effectiveness data supporting the use of onabotulinum-toxinA for the treatment of chronic migraine using the PREEMPT protocol. Although the authors pose the question "whether evidence-based advisory statements might be more helpful than a proscriptive protocol," 1 we suggest that, in contrast, there is robust evidence to support the PREEMPT protocol and its specific instructions and flexibility in dosing and injection sites that allow clinicians to use their judgment and tailor treatment to their individual patients.…”
Section: This Is An Open Access Article Under the Terms Of The Creativementioning
confidence: 81%
“…The authors conclude that over two-thirds of surveyed clinicians are altering the PREEMPT protocol, which calls into question the standardized nature of the protocol and suggests the creation of evidence-based advisory statements to discuss the protocol rationale. 1 We thank the authors for highlighting this important issue but believe that further clarification is needed about the evidence-based guidance and follow-thepain strategy described in previous PREEMPT injection protocol publications in Headache. 2,3 The authors report that 141/182 (78%) clinicians who responded to the survey (out of 878 contacted) reported not always following the PREEMPT protocol.…”
Section: Letter To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…Preclinical and clinical evidence have showed that BoNTs therapy had analgesic effects on neuropathic pain, trigeminal neuralgia, and chronic migraine (32). Notably, BoNT/A has been given official approval for preventive therapy of chronic migraine by Food and Drug Administration (FDA) in pain medicine (33). BoNTs can alleviate trigeminal neuralgia and can last for 6 months or more (34).…”
Section: Clinical Application Of Bonts In Neurologymentioning
confidence: 99%